(untitled) (Global Journal of Management and Business Research, 2019)
Indonesia Raya Incorporated (IRI) idea is a new and fascinating phenomenon in the perspective of the Indonesian economic system, mainly on the governance of State-owned Enterprises (SOEs) and Regional-owned Enterprises (ROEs). However, there are still few researchers who pay attention to their views on the IRI in corresponds to the Indonesia’s economic system and constitution. The purpose of this study was to reveal the relationship between the economic constitution and the roles and functions of state companies to describe the idea of IRI, and also identify and describe the variables included in the IRI concept. The study was carried out using qualitative methods, designed with narrative strategies and grounded theory, and interpreted by using the constructivism approach. The results of the study revealed that: (1) the idea of IRI was set in economic and social issues related to natural wealth governance and economic resources, which gave hope of fulfilling the mandate of the economic constitution through the role and function of SOEs and ROEs; and (2) the content of the IRI concept variable was the economic constitution, corporate strategy, government policy, company share ownership, and the role and function of the company. The description of these findings was translated theoretically, constructively and holistically, thus broadening the conception of IRI and having implications for the economic, management and business strategy.